Completing Baseline Mapping of Trachoma in Nepal: Results of 27 Population-Based Prevalence Surveys Conducted in 2013 and 2014. (28th December 2018) - Sharma, Shekhar; Ngondi, Jeremiah M.; Mishra, Sailesh; Prasad, Raman D.; Crowley, Kathryn; Bonuedi, Delali; Rotondo, Lisa A.; Nizigama, Lionel; Mosher, Aryc; Henry, Rob; Willis, Rebecca; Solomon, Anthony W.; et al.
ABSTRACT: Purpose : Trachoma is endemic in parts of Nepal; implementation of the surgery, antibiotics, facial cleanliness, environmental improvement (SAFE) strategy started in 2002. Some suspected-endemic districts had not previously been mapped. We aimed to estimate the prevalences of trachomatous inflammation—follicular (TF) and trichiasis in those districts. Methods : Population-based prevalence surveys were undertaken in 27 districts. In each of those districts, two-stage cluster sampling was used to select a sample of 2000 children aged 1–9 years and 4000 adults aged ≥15 years from a total of 40 wards (clusters), drawn evenly from two subdistricts. Consenting eligible participants were examined for trachoma by Global Trachoma Mapping Project (GTMP)-certified graders, using the World Health Organization simplified grading system. Data were analyzed at district level using GTMP methods. Results : A total of 43, 200 households were surveyed, and 162, 094 people were examined for trachoma. District-level TF prevalence in 1–9-year-olds ranged from 0% to 4.3% (95% confidence interval [CI] 2.4–6.2). Among adults aged ≥15 years, trichiasis prevalence ranged from 0% to 0.33% (95% CI 0.08–0.65). Conclusion : TF was not a public health problem in any of the 27 districts surveyed; thus, antibiotic mass drug administration is not needed. In two districts (Dhanusa and Gorkha), trichiasis prevalence in adults aged ≥15 years was ≥0.2%; thus, further trichiasis surgery interventions at public health level are warranted to achieve elimination. These findings will facilitate planning for elimination of trachoma as a public health problem in Nepal.